RANCANG BANGUN SISTEM POINT PELANGGAN PADA APOTIK BUCHORI CABANG BENGGALA DAN CIRUAS BANTEN - Yul Hendra; Rizki Fatullah (Jurnal Sistem Informasi dan Informatika (Simika), 2019)
As one way to increase the growth of the number of customers in a pharmacy, promotion needs to be done by giving awards to loyal customers, this is what underlies the Buchori Pharmacy wanting to develop a pharmacy information system that can accumulate customer points automatically. Previously the Buchori dispensary had an application for processing drug sales data however, the application does not have the customer's accumulated point feature automatically and does not yet have the customer's claim point feature, While these features have become a necessity for Buchori pharmacies to develop the system in the future. The methodology used in this study is the software engineering method by setting requirements and allocating needs into a computerized information system. This research is in order to develop an existing pharmacy information system in order to provide better satisfaction to customers, With the development of this information system, it is expected to be able to help operators and be able to provide satisfaction to Buchori pharmacy customers going forward.